Global Resources and Resource Justice—Reframing the Socioecological Science-to-Policy Landscape - Ioan Negrutiu (Resources)
The lexical analysis of seminal policy-to-diplomacy documents from the socio-environmental discourse of the last fifty years of agendas has allowed examining the contextual affinities between resources, pollution, and health. The central role of resource stewardship, according to nature’s physical limits, is highlighted in the context of the boundary systems for the biosphere and societies, and the carrying capacity and inclusive systemic health (one health, planetary health, …). To reframe a rather fragmented conceptual and methodological landscape, this work proposes choices that consider core values, purpose, and best practice developments, allowing us to compare the dynamics of socioecological states across the planet and in specific social, economic, political, and cultural contexts. The prioritization of resource justice and responsibility becomes a societal project, embedding the economy in social and ecological frames through institutional reframing and tangible action on resource management, pollution control, and health outcomes. How? By recognizing the primacy of the law and economy of life—the adequacy between basic needs and accessible resources for all— over the rules and economy of the market through socioecosystemic checks and balances.